Pengembangan Kompetensi Calon Guru PAI Dalam Pembuatan Butir Soal Kelas B Pendidikan Agama Islam (IAIN) Ponorogo - Amelia Junzho (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This research activity aims to increase the insight of prospective PAI teachers in making question items. The aim of this research is to increase the knowledge of prospective PAI teachers about how to create test items. Apart from that, this mentoring activity is expected to increase prospective teachers' knowledge about learning evaluation. Overall, it is hoped that this research can increase teacher innovation to improve the overall quality of learning. This research involves the Library research method. This activity is carried out during the course by creating questions in the Pai B class at IAIN Ponorogo. The activity ran smoothly with feedback from the lecturer who delivered the material and then the students who wrote the questions with full assistance and provided support in the question making process. Apart from that, the success of this activity can also be seen in the indicators that have been set.